Moored Temperature Observations in JASIN - DEWitt,L M; Bottero,J; Burt,W V; Paulson,C A; Simpkins,J (1980)
Moored temperature observations were obtained at an array of buoys in the North Atlantic (59 degrees 00.2'-59 degrees 10.7'N 12 degrees 27.4'-12 degrees 33.6'W) during the Joint Air-Sea Interaction Experiment (JASIN) of 1978. Observations were taken at 10-minute intervals by use of thermistors at 21 depths ranging from 4.5 m to 81.5 m. Plots of temperature as a function of time are presented for three moorings for the period July 28 through September 6, 1978.